Exploring Holistic Factors Shaping Undergraduate Engineering Student Development - Patil, Savita P.; Adamuthe, Amol C. (Journal of Engineering Education Transformations, 2025)
Promoting the holistic development of engineering students has become crucial in light of the knowledge economy's fast changing landscape and changing market dynamics. In order to create an ecosystem that supports students' performance in a variety of areas, educational institutions are essential. Numerous studies highlight different strategies for improving research skills, extracurricular involvement, and academic performance. However, variables like gender, resource availability, geographic location, and family background are all deeply entwined with the complexities of student development. The goal of this research paper is to provide a comprehensive framework for determining the various aspects affecting the development of undergraduate engineering students. Learning styles, reading comprehension, writing abilities, communication skills, leadership qualities, and research aptitude are all essential components of this framework. The main goal is to provide a thorough understanding of the complex interactions between these factors that influence students' overall development. An empirical study of 200 students from Rajarambapu Institute of Technology's Computer Science and Information Technology department is presented in this paper. The study makes use of student input gathered from carefully crafted surveys. These surveys are purposefully designed to identify barriers to students' growth. A variety of factors are revealed by the analysis, each of which has a unique effect on students' development. Adoption of a variety of learning styles, skillful technology integration, enthusiasm for blended Massive Open Online Courses (MOOCs), independent self-learning techniques, basic programming abilities, and critical soft skills are all considered positive attributes. The study, on the other hand, highlights drawbacks such as a lack of enthusiasm for research and entrepreneurship development, deficiencies in programming logic construction, a lack of confidence when speaking in front of an audience, a lack of leadership skills, fear of being judged, a lack of innovative ideas, and a reluctance to take risks.